The Impact of Economic Diversification on Supply Chain of Government Revenues: The Application on Gulf Cooperation Council Countries - dhannoon mohammed, Mohammed; salim ali, oday; mohammed sharef, Ashraf baderaddin (International Journal of Supply Chain Management, 2018)
Abstract- This paper examines and analyses evidence pertaining to economic diversification in the six countries (Kingdom of Saudi Arabia, United Arab Emirates, Oman, Qatar, Kuwait and Bahrain) comprising the Cooperation Council for the Arab States of the Gulf (GCC) countries (2005_2017). The purpose of the paper is to test to what extent these countries have recognized the importance of economic diversification in the process of the supply chain of government revenue and hence what are the measures adopted aiming at improving government revenue. Based on the evidence, the paper goes on to identify the determinants of economic diversification in the GCC countries. This paper uses recent growth theories and statistical techniques to empirically test for the association between economic diversification and supply chain of government revenue from the point of contribution from GDP in the GCC countries. Results obtained from data analysis indicate a strong relationship between economic diversification and supply chain of government revenue in the panel of the GCC. This result supports the endogenous growth hypothesis; at least for this group of countries. The Gulf Cooperation Council (GCC) countries share specific structural economic features. They depend heavily on the hydrocarbon sector, which was reflected in key macroeconomic indicators in 2014, as accounts for high budget receipts at 84 percent and approximately 69 percent of total GCC exports. Despite the huge accumulated financial surplus and the GCC governments’ investment in their economies, outcomes have fallen short of targets set out in their national visions, while the challenges of economic diversification persist. The overarching focus will be on the challenges of diversification in terms of strategic planning, policy-making, implementation, and global best practices. This study is expected to critically evaluate the current diversification strategies and underline some key assumptions that could lead, at a later stage, to the development of a new mode of diversification in the GCC context.